Transparent TPE (thermoplastic elastomer) material for encapsulating POM (polyoxymethylene) as well as preparation method and application of transparent TPE material

By using low molecular weight hydrogenated poly(styrene-b-butadiene-b-styrene) and silane-grafted styrene elastomer and acrylate block copolymer, transparent TPE material with encapsulated POM is solved. The problem of difficulty in having high transparency, excellent bonding performance and good processing performance has achieved efficient adhesive wrapping effect.

CN119463514AActive Publication Date: 2025-02-18KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202411735644.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

It is difficult to develop a transparent TPE material with a glued POM that has high transparency, excellent bonding and good processing properties, especially when covering POMs.

Method used

Modified by low molecular weight, low styrene content hydrogenated poly(styrene-b-butadiene-b-styrene) and silane-grafted styrene elastomer and acrylate block copolymer to form an encapsulated POM transparent TPE material.

Benefits of technology

The transparent TPE material with adhesive POM has high transparency, excellent adhesive properties and good processing properties, and solves the problem of poor POM coating effect of traditional TPE materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161402610000071
    Figure BDA0005161402610000071
  • Figure BDA0005161402610000072
    Figure BDA0005161402610000072
  • Figure BDA0005161402610000081
    Figure BDA0005161402610000081
Patent Text Reader

Abstract

The invention discloses a transparent TPE material for encapsulating POM and a preparation method of the transparent TPE material, and belongs to the technical field of thermoplastic elastomers. According to the invention, the styrene elastomer A with low molecular weight and low styrene content, the silane grafted styrene elastomer B and the acrylate block copolymer are adopted to prepare the POM-encapsulated transparent TPE material with high transparency, excellent adhesive property and good processability. The POM-encapsulated transparent TPE material obtained by the invention is suitable for the field of preparation of automobile parts and electric tool parts, and has a good market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermoplastic elastomers, and in particular relates to a transparent TPE material encapsulated with POM, and a preparation method and application thereof. Background Art

[0002] Polyoxymethylene (POM) is a linear polymer with no side chains, high density and high crystallinity. It has good physical, mechanical and chemical properties, especially excellent friction resistance. POM, commonly known as Saigang or Duogang, is the third largest general engineering plastic and is suitable for making wear-resistant parts, transmission parts, chemical and instrument parts.

[0003] POM encapsulation can combine the toughness and impact resistance of POM with the flexibility of thermoplastic elastomers, making the rigid POM substrate surface soft and having the characteristics of noise reduction, shock absorption, collision prevention, and anti-slip. However, due to its high crystallinity and extremely low surface friction coefficient, POM is the most difficult hard plastic to encapsulate in the industry, and encapsulation of POM has great technical difficulties.

[0004] At present, the TPE materials used for encapsulating rigid plastics on the market are mainly based on hydrogenated poly (styrene-b-butadiene-b-styrene) (SEBS), expansion oil, and filler. At the same time, polypropylene, polyethylene, or thermoplastic polyurethane elastomers are further added according to performance requirements. This type of TPE material often has an excellent encapsulation effect on general plastics, but the encapsulation effect on POM is not satisfactory. It has the characteristics of low fluidity, poor processability, poor encapsulation adhesion, and easy peeling.

[0005] In addition, when used in industries such as automobiles and home appliances that have high requirements for aesthetics, POM products are best to have a certain degree of transparency. However, given the difficulty of encapsulating POM, it is still a major problem in this field to balance the adhesion and transparency of encapsulated POM products.

[0006] Therefore, developing a transparent TPE material encapsulated with POM that has high transparency, excellent bonding properties and good processing properties has important research significance and application value. Summary of the invention

[0007] In order to solve the technical problem that the TPE material encapsulated with POM in the prior art is difficult to achieve high transparency, excellent bonding performance and good processing performance, the primary purpose of the present invention is to provide a transparent TPE material encapsulated with POM. The TPE material provided by the present invention adopts a styrene elastomer A with a low molecular weight and low styrene content, and is modified together with a silane-grafted styrene elastomer B and an acrylate block copolymer to obtain a transparent TPE material encapsulated with POM that has high transparency, excellent bonding performance and good processing performance.

[0008] Another object of the present invention is to provide a method for preparing the transparent TPE material encapsulated with POM.

[0009] Another object of the present invention is to provide the application of the transparent TPE material encapsulated with POM in the field of preparing automobile parts and electric tool parts.

[0010] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0011] A transparent TPE material encapsulated with POM, comprising the following components in parts by weight: 20-30 parts of styrene elastomer A, 10-20 parts of styrene elastomer B, 10-20 parts of acrylate block copolymer, and 20-40 parts of filler oil;

[0012] Wherein, the styrene elastomer A is hydrogenated poly(styrene-b-butadiene-b-styrene);

[0013] The styrene elastomer B is silane-grafted hydrogenated poly(styrene-b-butadiene-b-styrene);

[0014] The weight average molecular weight of the styrene elastomer A is 30,000 to 100,000, and the styrene content is 10% to 20%;

[0015] The weight average molecular weight of the styrene elastomer B is ≥100,000 and the styrene content is 28-32%.

[0016] The present invention provides a transparent TPE material encapsulated with POM, wherein low molecular weight and low styrene content hydrogenated poly (styrene-b-butadiene-b-styrene) is selected, which has good fluidity and can give the TPE material good transparency and fluidity; the addition of silane grafted hydrogenated poly (styrene-b-butadiene-b-styrene) can give the TPE material adhesion and moderate mechanical properties; the acrylate block copolymer can be used in conjunction with silane grafted hydrogenated poly (styrene-b-butadiene-b-styrene) on the one hand to synergistically provide POM adhesion performance, and can be used in conjunction with hydrogenated poly (styrene-b-butadiene-b-styrene) on the other hand to synergistically improve transparency. Silane grafted hydrogenated poly (styrene-b-butadiene-b-styrene) needs to be selected with high molecular weight and high styrene content so as to be fully mixed with filler oil. Insufficient mixing will lead to poor fluidity of the TPE material, thereby ultimately affecting the adhesion performance.

[0017] The method for determining the weight average molecular weight of the present invention refers to GB / T 27843-2011, the solvent is tetrahydrofuran, the chromatographic column is a THF type chromatographic column; and the styrene content is determined by nuclear magnetic resonance.

[0018] Preferably, the mass percentage of the styrene elastomer A in the composition is not less than 24.5%.

[0019] Specifically, the styrene-based elastomer B is obtained by melt grafting hydrogenated poly(styrene-b-butadiene-b-styrene) with silane.

[0020] Preferably, the silane grafting rate of the styrene elastomer B is 0.1-2 wt %, preferably 0.5-0.8 wt %.

[0021] Specifically, the silane is a silane coupling agent containing a carbon-carbon double bond or a carbon-carbon triple bond, and is selected from at least one of vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltri(β-methoxyethoxy)silane.

[0022] Preferably, the acrylic ester block copolymer is selected from at least one of methyl methacrylate-acrylate-methyl methacrylate block copolymer and ethylene-butyl acrylate copolymer.

[0023] Specifically, the methyl methacrylate-acrylic ester-methyl methacrylate block copolymer is selected from at least one of methyl methacrylate-methyl acrylate-methyl methacrylate block copolymer, methyl methacrylate-ethyl acrylate-methyl methacrylate block copolymer, methyl methacrylate-propyl acrylate-methyl methacrylate block copolymer or methyl methacrylate-butyl acrylate-methyl methacrylate block copolymer.

[0024] Preferably, the TPE material further comprises an antioxidant and / or an amide lubricant, specifically, 0.1-1 part of the antioxidant and 0-2 parts of the amide lubricant.

[0025] In order to ensure the transparency of the TPE material, the present invention selects amide lubricants.

[0026] Preferably, the amide lubricant is selected from at least one of erucamide and oleamide.

[0027] Preferably, the antioxidant is selected from at least one of antioxidant 1010 and antioxidant 168, preferably a composite antioxidant of the antioxidant and antioxidant 168, and preferably the mass ratio of antioxidant 1010 to antioxidant 168 is 1:2 to 1:5.

[0028] Specifically, the filler oil is white oil. More specifically, the kinematic viscosity of the white oil is 90 to 100 mm 2 / s, open flash point ≥260℃.

[0029] The present invention also provides a method for preparing a transparent TPE material encapsulated with POM, comprising the following steps:

[0030] The filler oil is pre-mixed with the styrene elastomer B at a low speed, and then mixed with the styrene elastomer A, the acrylate block copolymer and other additives at a high speed; the mixed raw materials are melt-extruded, cooled and granulated to obtain the transparent TPE material encapsulated with POM.

[0031] Preferably, the melt extrusion conditions are: melt extrusion temperature is 170-180° C., extrusion process residence time is 50-80 s, moisture content is ≤0.5%, the aspect ratio of the twin-screw extruder is 40-56:1, and the screw speed is 200-300 rpm.

[0032] The melt extrusion process requires strict control of moisture.

[0033] The application of the above-mentioned transparent TPE material encapsulated with POM in the preparation of automobile parts or electric tool parts is also within the protection scope of the present invention.

[0034] Preferably, the transparent TPE material encapsulated with POM is used in the preparation of automobile seals, automobile shock absorbers or handle protection covers of electric tools.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The transparent TPE material for encapsulating POM provided by the present invention selects SEBS with low molecular weight and low styrene content to maintain good processing performance and transparency; the performance of bonding POM is improved by silane-grafted styrene elastomer and acrylate block copolymer, and the obtained transparent TPE material for encapsulating POM has the advantages of high transparency, excellent bonding performance and good processing performance. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.

[0038] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:

[0039] The styrene content and weight average molecular weight of the following hydrogenated poly(styrene-b-butadiene-b-styrene) are self-measured values, and the determination method is as follows:

[0040] Styrene content determination method: NMR;

[0041] The method for determining the weight average molecular weight is as follows: GB / T 27843-2011. The solvent is tetrahydrofuran and the chromatographic column is a THF type chromatographic column.

[0042] SEBS-A 1#: hydrogenated poly(styrene-b-butadiene-b-styrene), brand G1657, manufacturer Kraton, styrene content of 14%, weight average molecular weight of 60,000;

[0043] SEBS-A 2#: hydrogenated poly (styrene-b-butadiene-b-styrene), brand name YH-510, manufacturer Yuehua, styrene content is 20%, weight average molecular weight is 80,000;

[0044] SEBS-A 3#: hydrogenated poly(styrene-b-butadiene-b-styrene), brand MD1646, manufacturer Kraton, styrene content of 13%, weight average molecular weight of 50,000;

[0045] SEBS-A 4#: hydrogenated poly (styrene-b-butadiene-b-styrene), brand name YH-506, manufacturer Yuehua, styrene content is 13%, weight average molecular weight is 150,000;

[0046] SEBS-A 5#: hydrogenated poly(styrene-b-butadiene-b-styrene), brand G1642, manufacturer Kraton, styrene content of 22.5%, weight average molecular weight of 100,000;

[0047] SEBS-B 1#: hydrogenated poly (styrene-b-butadiene-b-styrene): brand G1654, manufacturer Kraton; styrene content is 30%, weight average molecular weight is 150,000; silane grafting: vinyl triethoxysilane, SICO-V151, Silicon Science New Materials; grafting rate is 0.6wt%;

[0048] SEBS-B 2#: Hydrogenated poly (styrene-b-butadiene-b-styrene): brand name YH-688, manufacturer Yuehua; styrene content is 15%, weight average molecular weight is 180,000; silane grafting: vinyl triethoxysilane, brand name SICO-V151, manufacturer Si Ke Xincai; silane grafting rate is 0.6wt%;

[0049] SEBS-B 3#: Hydrogenated poly (styrene-b-butadiene-b-styrene): brand A1536HS, manufacturer Kraton; styrene content is 40%, weight average molecular weight is 150,000; silane grafting: vinyl triethoxysilane, SICO-V151, Silicon Science New Materials; silane grafting rate is 0.6wt%;

[0050] SEBS-B 4#: Hydrogenated poly(styrene-b-butadiene-b-styrene): brand G1654, manufacturer Kraton, styrene content 30%, weight average molecular weight 150,000, no grafting;

[0051] SEBS-B 5#: hydrogenated poly(styrene-b-butadiene-b-styrene): brand G1654, manufacturer Kraton; styrene content 30%, weight average molecular weight 150,000; maleic anhydride grafted; maleic anhydride grafting rate 0.6wt%;

[0052] SEBS-B 6#: Hydrogenated poly (styrene-b-butadiene-b-styrene): brand G1652, manufacturer Kraton; styrene content is 30%, weight average molecular weight is 80,000; silane grafting: vinyl triethoxysilane, SICO-V151, Silicon Science New Materials; silane grafting rate is 0.6wt%;

[0053] Acrylate block copolymer 1#: methyl methacrylate-butyl acrylate-methyl methacrylate block copolymer, KURARITY TM LA4285, Kuraray;

[0054] Acrylate block copolymer 2#: ethylene-butyl acrylate copolymer (EBA), EBAREPSOL E1704, Lepsol, Spain;

[0055] Filling oil: white oil, PW-90, Idemitsu, Japan;

[0056] Lubricant: erucamide lubricant, commercially available;

[0057] Antioxidants: Antioxidant 1010, Antioxidant 168, commercially available; the mass ratio of Antioxidant 1010 to Antioxidant 168 is 1:3.

[0058] SEBS-B 1#~SEBS-B 3# are prepared by the following process:

[0059] In the premixing section of the extruder, the components were uniformly mixed according to the ratio of 15 mmol silane / 15 mmol diisopropylbenzene peroxide / 100 g hydrogenated poly(styrene-b-butadiene-b-styrene), and put into a twin-screw machine for melt grafting. The extrusion temperature was 190° C. and the rotation speed was 200 rpm.

[0060] SEBS-B 5# is prepared by the following process:

[0061] In the premixing section of the extruder, a certain amount of maleic anhydride, 15 mmol of diisopropylbenzene peroxide, 100 g of hydrogenated poly(styrene-b-butadiene-b-styrene) and other components were uniformly mixed and put into a twin-screw machine for melt grafting. The extrusion temperature was 190°C and the rotation speed was 200 rpm.

[0062] The transparent TPE material encapsulated with POM in each embodiment of the present invention and the comparative example is prepared by the following process:

[0063] The white oil is pre-mixed with the styrene elastomer B at a low speed, and then mixed with the styrene elastomer A, the acrylic block copolymer, the filler and other additives in a high-speed mixer at a high speed; the mixed raw materials are added to a twin-screw extruder, and after melt extrusion, they are cooled and granulated to obtain the transparent TPE material encapsulated with POM;

[0064] The melt extrusion conditions of the twin-screw extruder are as follows: the raw material is dried at 80°C for 12 hours, the moisture content is ≤0.5%, the melt extrusion temperature is 200°C, the residence time of the extrusion process is 80 seconds, the aspect ratio of the twin-screw extruder is 40:1, and the screw speed is 300rpm.

[0065] Comparative Example 6: The white oil was pre-mixed with SEBS-B 4# at a low speed, and then mixed with vinyl triethoxysilane, diisopropylbenzene peroxide, styrene elastomer A, acrylate block copolymer, filler and other additives in a high-speed mixer at a high speed; the mixed raw materials were added to a twin-screw extruder, and after melt extrusion, they were cooled and granulated to obtain the transparent TPE material encapsulated with POM, wherein the addition ratio of vinyl triethoxysilane and diisopropylbenzene peroxide was 15 mmol of silane / 15 mmol of diisopropylbenzene peroxide / 100 g of SEBS-B 4#;

[0066] The melt extrusion conditions of the twin-screw extruder are as follows: the raw material is dried at 80°C for 12 hours, the moisture content is ≤0.5%, the melt extrusion temperature is 200°C, the residence time of the extrusion process is 80 seconds, the aspect ratio of the twin-screw extruder is 40:1, and the screw speed is 300rpm.

[0067] Comparative Example 7: The white oil is pre-mixed with SEBS-B 5# at a low speed, and then mixed with the styrene elastomer A, the acrylic block copolymer, the filler and other additives in a high-speed mixer at a high speed; the mixed raw materials are added to a twin-screw extruder, and after melt extrusion, cooled and granulated to obtain the transparent TPE material encapsulated with POM;

[0068] The melt extrusion conditions of the twin-screw extruder are as follows: the raw material is dried at 80°C for 12 hours, the moisture content is ≤0.5%, the melt extrusion temperature is 200°C, the residence time of the extrusion process is 80 seconds, the aspect ratio of the twin-screw extruder is 40:1, and the screw speed is 300rpm.

[0069] The performance testing methods and standards of the transparent TPE materials of the embodiments and comparative examples of the present invention are as follows:

[0070] The particle material prepared according to the above method was dried in a forced air oven at 75°C for 3 hours, and then the dried particles were made into standard specimens on an injection molding machine for testing.

[0071] (1) Shore hardness (A): Refer to ISO 7619-2012 standard, where the reading time is 15 seconds.

[0072] (2) Peel force (N / mm): Refer to VDI 2019 standard, where the soft glue thickness is 2.0 mm.

[0073] (3) Transparency: Refer to GB / T 2410-2008 standard, where the thickness is 2.0 mm.

[0074] (4) Melt index MI (g / 10 min): refer to ISO 1133-2011 standard, where the test conditions are 230°C / 2.16 kg.

[0075] Examples 1 to 11

[0076] This embodiment provides a series of transparent TPE materials encapsulated with POM, and the weight proportions of the components in the formula are shown in Tables 1 and 2.

[0077] Table 1 Examples 1 to 3 formulations (parts)

[0078]

[0079] Table 2 Examples 3 to 11 formulations (parts)

[0080]

[0081] Comparative Examples 1 to 10

[0082] This comparative example provides a series of transparent TPE materials encapsulated with POM, and the components in the formula are shown in Table 3.

[0083] Table 3 Formulas of Comparative Examples 1 to 10 (parts)

[0084]

[0085] The performance test results of the transparent TPE material encapsulated with POM in each embodiment and comparative example according to the above-mentioned method are shown in Table 4.

[0086] Table 4 Performance test results of various embodiments and comparative examples

[0087]

[0088]

[0089] It can be seen from Table 4 that the transparent TPE materials encapsulating POM prepared in Examples 1 to 11 of the present invention all have the characteristics of high transparency, excellent bonding performance and good processing performance, wherein the transparency is higher than 65%, the peel force is higher than 2 N / mm, the melt flow rate is higher than 9 g / 10 min, and the hardness is 40 to 70A.

[0090] The weight average molecular weight of the styrene elastomer A used in Comparative Example 1 is too high and its fluidity is poor, which, on the one hand, leads to poor fluidity of the TPE material, thereby reducing the peeling force, and on the other hand, leads to reduced transparency of the TPE material; the styrene content of the styrene elastomer A used in Comparative Example 2 is too high, resulting in poor transparency; Comparative Example 3 does not add styrene elastomer A, and the fluidity of the TPE material is very poor, resulting in various properties of the TPE material not meeting expectations; Comparative Example 4 does not add styrene elastomer B to provide main body adhesion to the TPE material, and the peeling force of the TPE material is basically zero; Comparative Example 5 does not add acrylate block copolymer, on the one hand, the styrene elastomer B lacks the synergistic effect of adhesion, resulting in low adhesion of the TPE material, and on the other hand, the styrene elastomer A lacks the synergistic effect of transparency, resulting in low transparency of the TPE material; Comparative Example 6 Instead of adding silane-grafted styrene elastomer B, ungrafted styrene elastomer B, silane and other components are directly blended during the preparation of the TPE material. Silane and ungrafted styrene elastomer B cannot be effectively grafted, resulting in almost no adhesion between the TPE material and POM, and the peeling force is basically zero; Comparative Example 7 adds maleic anhydride-grafted styrene elastomer B, which has no adhesion to POM, resulting in the peeling force of the TPE material being basically zero; the styrene content of the styrene elastomer B added in Comparative Example 8 is too low, resulting in the inability of the styrene elastomer B to absorb the filling oil and the TPE material cannot be formed; the styrene content of the styrene elastomer B added in Comparative Example 9 is too high, resulting in low transparency of the TPE material; the weight-average molecular weight and mechanical strength of the styrene elastomer B added in Comparative Example 10 are too low, resulting in low peeling force of the TPE material.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A transparent TPE material encapsulated with POM, characterized in that: The invention comprises the following components in parts by weight: 20-30 parts of styrene elastomer A, 10-20 parts of styrene elastomer B, 10-20 parts of acrylate block copolymer, and 20-40 parts of filler oil; Wherein, the styrene elastomer A is hydrogenated poly(styrene-b-butadiene-b-styrene); The styrene elastomer B is silane-grafted hydrogenated poly(styrene-b-butadiene-b-styrene); The weight average molecular weight of the styrene elastomer A is 30,000 to 100,000, and the styrene content is 10% to 20%; The weight average molecular weight of the styrene elastomer B is ≥100,000 and the styrene content is 28-32%.

2. According to claim 1, the transparent TPE material encapsulated with POM is characterized in that: The styrene elastomer B is obtained by melt grafting hydrogenated poly(styrene-b-butadiene-b-styrene) with silane.

3. The transparent TPE material encapsulated with POM according to claim 1 or 2, characterized in that: The silane grafting rate of the styrene elastomer B is 0.5-0.8 wt %.

4. The transparent TPE material encapsulated with POM according to claim 1 or 2, characterized in that: The silane is a silane coupling agent containing a carbon-carbon double bond or a carbon-carbon triple bond.

5. The transparent TPE material encapsulated with POM according to claim 1, characterized in that: The acrylic acid ester block copolymer is selected from at least one of methyl methacrylate-acrylic acid ester-methyl methacrylate block copolymer and ethylene-butyl acrylate copolymer.

6. The transparent TPE material encapsulated with POM according to claim 5, characterized in that: The methyl methacrylate-acrylic ester-methyl methacrylate block copolymer is selected from at least one of methyl methacrylate-methyl acrylate-methyl methacrylate block copolymer, methyl methacrylate-ethyl acrylate-methyl methacrylate block copolymer, methyl methacrylate-propyl acrylate-methyl methacrylate block copolymer, and methyl methacrylate-butyl acrylate-methyl methacrylate block copolymer.

7. The transparent TPE material encapsulated with POM according to claim 1, characterized in that: The filler oil is white oil.

8. The transparent TPE material encapsulated with POM according to claim 1, characterized in that: The transparent TPE material further comprises an antioxidant and / or an amide lubricant.

9. The method for preparing the transparent TPE material encapsulated with POM according to any one of claims 1 to 8, characterized in that: The following steps are involved: The filler oil is pre-mixed with the styrene elastomer B at a low speed; then mixed with the styrene elastomer A, the acrylate block copolymer, the filler and other additives at a high speed; the mixed raw materials are melt-extruded, cooled and granulated to obtain the transparent TPE material encapsulated with POM.

10. Use of the transparent TPE material encapsulated with POM according to any one of claims 1 to 8 in the preparation of automobile parts or electric tool parts.

Citation Information

Patent Citations

  • TPE (thermoplastic elastomer) material for encapsulating POM (polyformaldehyde) as well as preparation method and application of TPE material

    CN108219483A

  • TPE rubber coating compound for PCTG plastic and preparation method thereof

    CN109294150A

  • TPE material for bonding polyformaldehyde (POM) and preparation method of TPE material

    CN110746915A

  • Low-temperature-resistant TPE (Thermoplastic Elastomer) material for encapsulating resin, encapsulated product as well as preparation method and application of encapsulated product

    CN118307924A

  • Hydrogenated block copolymer, hydrogenated block copolymer composition, and molding

    JP2024112770A

Cited By

  • Transparent TPE material for encapsulating POM, and preparation method therefor and use thereof

    WO2026114309A1